Ireland and Cultural Theory - Graham, Colin. author. aut Link
XI, 249 p.
Keywords: Ireland and Cultural Theory is a unique and timely collection offering the first major assessment of how theoretical readings of 'Ireland' and Irish culture have begun to question the grounds of debate in Irish studies. Contributions engage with the concept of the 'authentic' in Irish culture through analyses of film, television and literature, emigration, and institutional critical practice. This lively and challenging volume will be of interest to lecturers and students in the field of cultural studies, Irish studies and critical theory.